Pilot Study Revealed Association of DRD4 Promoter Variants with ADHD Associated Functional Deficit in Indian Probands (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: ADHD; molecular genetics; cognitive impairment; learning difficulties